2014
DOI: 10.1371/journal.pone.0085516
|View full text |Cite
|
Sign up to set email alerts
|

Blunted Response to Combination Antiretroviral Therapy in HIV Elite Controllers: An International HIV Controller Collaboration

Abstract: ObjectiveHIV “elite controllers” (ECs) spontaneously control viral load, but some eventually require combination antiretroviral treatment (cART), due to a loss of viral control or a decline in CD4 T-cell counts. Here we studied the CD4 T-cell count dynamics after cART initiation among 34 ECs followed in U.S. and European cohorts, by comparison with chronically viremic patients (VIRs).MethodsECs were defined as patients with at least ≥5 viral load (VL) measurements below 400 copies/mL during at least a 5-year p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 31 publications
0
20
0
3
Order By: Relevance
“…In this population, the etiology of CD4 + T cell decline may be multifactorial because T-cell activation has also been found to be associated with lower CD4 + cell counts [ 12 ]. It is interesting to note that although initiation of ART in HIV controllers has resulted in diminished HIV reservoir size [ 46 ], lower levels of residual viremia, and T-cell activation [ 38 ], it is only associated with a modest or no increase in CD4 + cell counts [ 38 , 47 ]. The etiology behind this blunted CD4 + cell response to ART remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In this population, the etiology of CD4 + T cell decline may be multifactorial because T-cell activation has also been found to be associated with lower CD4 + cell counts [ 12 ]. It is interesting to note that although initiation of ART in HIV controllers has resulted in diminished HIV reservoir size [ 46 ], lower levels of residual viremia, and T-cell activation [ 38 ], it is only associated with a modest or no increase in CD4 + cell counts [ 38 , 47 ]. The etiology behind this blunted CD4 + cell response to ART remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…These individuals, termed HIV controllers, represent a rare group whose HIV-specific immune responses enable them to control the virus without ART (Migueles and Connors 2015; Walker and Yu 2013). Despite evidence of ongoing virus replication in HIV controllers not receiving ART (Boufassa et al 2014; Chun et al 2013; Fukazawa et al 2015; Hatano et al 2013; Mens et al 2010; OConnell et al 2010; Salgado et al 2010), prior work has shown fewer CD4 T cells containing HIV DNA (Julg et al 2010) and replication-competent HIV (Blankson et al 2007) in HIV controllers than in non-controllers. We reasoned that this would allow us to sample more of the total virus population in these individuals and therefore obtain a comprehensive view of the infected CD4 T cell pool.…”
Section: Introductionmentioning
confidence: 99%
“…However, some HICs eventually exhibit a decline in their CD4+ T cell count during the period of HIV control and/or lose the ability to control HIV [ 11 , 12 ]. Using ultrasensitive techniques, low levels of HIV replication can be detected in HICs and might be correlated with the CD4+ T cell loss [ 11 , 13 ].…”
Section: Introductionmentioning
confidence: 99%